IMPLEMENTASI SOSIALISASI DAN PROMOSI POLA KONSUMSI PANGAN BERAGAM, BERGIZI, SEIMBANG DAN AMAN (B2SA) PADA PEKARANGAN DI KOTA PEKANBARU STUDI KASUS: PERCEPATAN PENGANEKARAGAMAN KONSUMSI PANGAN (P2KP) - Tresna Widyawati; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Implementation Rules of Mayor in Pekanbaru Number 66 Year 2012 about Implementation of Food Consumption Diversification Acceleration based on Local food Still Not optimal. Until The year of 2013, Pekanbaru’s food consumption quality has not met it’s ideal pattern yet shown by DDP (Desirable Dietary Pattern) Score 71.84 compared with national ideal score of 95. Public Still not know the role of local food as a support food security and nutrition requirement of the household family can be seen from the lack of public knowledge about the P2KP Program to utilize the garden as a source of food. This happens due to the lack of socialization received by the public about P2KP program. The research aims to identify and analyze the implementation of socialization and promotion of food consumption patterns varied, nutritious, balanced and safe (B2SA) conducted by the Food Security and Implementation of Agricultural Extension (BKPDP3) Pekanbaru City and the factors that influence it.This research using communication theory by Laswell which includes five elements is: communicators, media, messages, communicant and effect. This study usesdescriptive qualitative research methods. In collecting the data, the researcher used dept interview, observation, and document and then using key informants as a source of information.The results showed that socialization has been done by BKPDP3 Pekanbaru City is still not optimal. Many people do not understand the importance of the ideal food pattern and utilization oflocal resources as a source of food. So far DDP score has not reached the ideal conditionsKeywords: Implementation, Socialization, Promotion, P2KP